Potent α-glucosidase and α-amylase inhibitory activities of standardized 50% ethanolic extracts and sinensetin from Orthosiphon stamineus Benth as anti-diabetic mechanism - Mohamed Elsnoussi Ali; Siddiqui Mohammad Jamshed; Ang Lee; Sadikun Amirin; Chan Sue; Tan Soo; Asmawi Mohd; Yam Mun (BMC, 2012)
Abstract Background In the present study, we tested a 50% ethanolic extract of Orthosiphon stamineus plants and its isolated bioactive compound with respect to their α-glucosidase and α-amylase inhibitory activities. Methods Bioactive flavonoid sinensetin was isolated from 50% ethanolic extract of Orthosiphon stamineus. The structure of this pure compound was determined on the NMR data and the α-glucosidase and α-amylase inhibitory activities of isolated sinensetin and 50% ethanolic extract of Orthosiphon stamineus were evaluated. Results In vitro studies of a 50% ethanolic extract of O. stamineus and the isolated sinensetin compound showed inhibitory activity on α-glucosidase (IC50: 4.63 and 0.66 mg/ml, respectively) and α-amylase (IC50: 36.70 mg/ml and 1.13 mg/ml, respectively). Inhibition of these enzymes provides a strong biochemical basis for the management of type 2 diabetes via the control of glucose absorption. Conclusion Alpha-glucosidase and α-amylase inhibition could the mechanisms through which the 50% ethanolic extract of O. stamineus and sinensetin exert their antidiabetic activity, indicating that it could have potential use in the management of non-insulin-dependent diabetes.